A Stack-Slicing Algorithm for Multi-Core Model Checking - Holzmann, Gerard J. (Electronic notes in theoretical computer science, 2008)
The broad availability of multi-core chips on standard desktop PCs provides strong motivation for the development of new algorithms for logic model checkers that can take advantage of the additional processing power. With a steady increase in the number of available processing cores, we would like the performance of a model checker to increase as well – ideally linearly. The new trend implies a change of focus away from cluster computers towards shared memory systems. In this paper we discuss the multi-core algorithms that are in development for the SPIN model checker.